DIGITAL MARKETING TO CUSTOMER VALUE AND CUSTOMER ENGAGEMENT IN REPEAT PURCHASE ON THE MARKETPLACE - Susanti, Desi (SULTANIST: Jurnal Manajemen dan Keuangan, 2021)
Digital marketing is the use of electronic media by marketers to promote products or services to the market. With the popularity of broadband Internet and the rapid development of network technology in recent years, traditional marketing has also gradually shifted to digital marketing. Likewise, consumers have started to look and be interested and switch to the marketplace. This study examines the influence of digital marketing on the marketplace. In digital marketing activities, of course, it cannot be separated from the exchange of consumer values (customer value) and the formation of engagement (customer engagement). This research was conducted by distributing questionnaires to 200 people who made repeated purchases at the marketplace in Riau Province. The results of the observations will be analyzed using the Structural Equation Model (SEM) method. The results of the analysis using the Structural Equation Model (SEM) conclude that digital marketing has a direct influence on customer value and customer engagement in the marketplace. Customer value and customer engagement have a direct influence on repeat purchases in the marketplace. And digital marketing has an indirect influence on repeat purchases through customer value and customer engagement in the marketplace.